Effect of Symmetry Breaking on Interlayer Exchange Coupling and Electrical Conduction in SrRuO3–PrMnO3 Superlattices. Issue 20 (20th August 2018) - Sahoo, Antarjami; Prellier, Wilfrid; Padhan, Prahallad
Abstract: The breaking of orthorhombic to tetragonal crystal symmetry is realized by increasing the PrMnO3 layer thickness in the superlattices consisting two ferromagnets, SrRuO3 and PrMnO3 . The octahedral rotation pattern is a + c − c − and a 0 a 0 c − type for the superlattices with orthorhombic and tetragonal phase, respectively, inferred in the simulated projected density of states. The 15% reduction in d z 2 orbital occupancy due to the a 0 a 0 c − type octahedral rotation compared to that of the a + c − c − type suggests the presence of stronger antiferromagnetic (AFM) coupling. The larger orbital overlapping leads to a stronger spin–orbit coupling, associated with a shift of 42.8% of the minor in‐plane field cooled (FC) magnetic hysteresis loop(M(H)) along the magnetization axis in orthorhombic superlattices. While, minor in‐plane FC M(H) shifts along the field axis due to the strong AFM coupling in tetragonal superlattices. In field‐dependent magnetoresistance, the rotation of spins in the antiferromagnetically coupled interfacial layers is detected as a unique anomaly, which is stronger in the superlattices for the biased spins and tetragonal symmetry than the pinned spins and orthorhombic symmetry. The results demonstrate that the tuning of interfacial exchange coupling and spin‐dependent transport by controlling structural distortion could be used as a tool in fabricating modern spintronics‐based devices. Abstract : The size effect in SrRuO3 /PrMnO3 superlattices is used to induce orthorhombic‐to‐tetragonal crystal symmetry breaking. In orthorhombic superlattices, the larger orbital overlapping leads to a stronger spin–orbit coupling, which shifts minor in‐plane field‐cooled (FC) magnetic hysteresis loop (M(H)) 42.8% along the magnetization axis. While, minor in‐plane FC M(H) shifts 0.0368T along the field axis due to the strong antiferromagnetic coupling in tetragonal superlattices.